Mitral and Tricuspid Transcatheter Interventions Current Indications and Future Directions - Winkel, Mirjam Gauri; Praz, Fabien; Wenaweser, Peter (Frontiers in Cardiovascular Medicine, 2020)
Introduction Valvular heart disease (VHD) is a common condition that has long been underappreciated although it has enormous impact on mortality and morbidity. Population-based analyses have shown a prevalence of moderate to severe mitral and tricuspid valve disease of 9.3% and 4.0% in the ageing population, respectively. [1, 2] The incremental annual costs for VHD in the US are substantial (estimated at $23.4 billion [3]) and expected to further increase given population growing and aging. In the past, a high proportion of patients with severe mitral or tricuspid valve disease has been denied treatment beyond medical therapy, mainly because of age and decreased left ventricular function that are both associated with high surgical risk.[4] Over the last years, the interventional landscape has widely expanded with new transcatheter methods emerging for both mitral and tricuspid valve treatment. In contrast to transcatheter aortic valve implantation (TAVI), the interventional treatment of mitral and tricuspid valve disease requires a substantially more versatile approach due to the different etiologies of valvular dysfunction. This paper aims to review the evolution of the field, to discuss current indications and limitations and attempts to provide a glimpse to the future of transcatheter interventions for mitral and tricuspid valve disease.